Green Synthesis and Nanotoxicity Assay of Copper-Cobalt Bimetallic Nanoparticles as a Novel Nanolarvicide for Mosquito Larvae Management - Shehu, Zaccheus; Danbature, Wilson Lamayi; Magaji, Buhari; Adam, Muhammad Mustapha; Bunu, Musa Aminu; Mai, Abigail John; Mela, Yoro (The International Journal of Biotechnology, 2020)
Plant mediated nanoparticles have been investigated to possess many applications in many fields such as pharmaceuticals, therapeutics and other commercial products. In this study, Copper/Cobalt bimetallic nanoparticles were synthesized by an eco-friendly and cost effective method using Palmyra palm fruit extract and characterized using various techniques such as UV-visible spectrophotometry and Fourier transform infrared spectrometry. Green synthesis method was used in obtaining the nanoparticles and the agar well diffusion method was used in evaluating the larvicidal activity. The resulting nanoparticles were evaluated to find possible application as nanolarvicide against first, second and third instar of Culex quinquefasciatus larvae in terms of percentage mortality. The lethal concentration values were LC50=12.036, LC90=143.316; LC50=14.774, LC90=263,456; LC50=16.076, LC90=296.758 ppm for the first, second, and third instars respectively implying moderate activity of this copper/cobalt nanoparticles. It could be concluded that copper-cobalt bimetallic nanoparticles synthesized using fruit extract of palmyra palm could be a potential nanolarvicide for mosquito larvae management.